EMERGENCY NOTIFICATION AND COMMUNICATION MECHANISM (International Conference on Economics, Finance, Banking and Management, 2025)
In the article we will consider the main tasks of providing communication and notification in emergency situations, mechanisms for organizing communication and alerting the population.